Jurnalisme Antar Budaya Sebagai Jalan Menuju Toleransi Berbangsa dan Bernegara - Richard G Mayopu (PAX HUMANA, 2015)
Indonesian Journalism has shown increased after the collapse of new order. Freedom of the press who fought for so long, successfully obtained with full of struggle. However, the use of freedom of the press is apparently still erroneous and inaccurate. The mass media are supposed to be part of the development of the nations character and religious tolerance, but in Fact, Mass media gave the impression that they did not care about the impact of journalism message. This article aims to explain and describe how tolerance in Indonesia could be built and escorted by journalism in Indonesia. Finally, the results of this paper is that the use of the phrase journalism shows that is not aware of the cultural diversity, and this things would be a time bomb in Indonesian society of tolerance and diversity.Keywords:Jurnalism, Culture, Tolerance